Effects of Transgenic Rice Infected with SRBSDV on Bt expression and the Ecological Fitness of Non-vector Brown Planthopper Nilaparvata lugens - Hong-Xing Xu (Nature Portfolio, 2017)
Abstract The susceptibility of rice lines, T1C-19, T2A-1, and MH63 to SRBSDV infection are similar and the contents of cry protein in T2A-1 and T1C-19 do not change significantly. The survival rates of BPH nymphs feeding on SRBSDV-infected T1C-19, Bt T2A-1, or MH63 rice plants were not significantly different. The developmental stages of female BPH fed on T1C-19 plants infected with SRBSDV were significantly shorter than those fed on uninfected rice, while the males showed no significant difference. The duration of BPH feeding on SRBSDV-infected T2A-1 and MH63 also showed no significant difference in comparison with the respective control groups. Longevities of BPH adults feeding on SRBSDV-infected T1C-19, T2A-1 or MH63 were also not significant. However, the longevity of male adult BPH feeding on un-infected MH63 was significantly reduced in comparison with that of adult males feeding on un-infected T1C-19 and T2A-1 rice. In addition, the different rice lines and the rice plants infected and uninfected with SRBSDV did not significantly affect the sex ratio, female body weight, longevity, fecundity, or egg hatchability of BPH. In general, transgenic Bt rice infected with SRBSDV had little effect on the ecological adaptability of BPH.